Penguatan Kapasitas Produksi “Ummah Cookies” melalui Pengembangan Produk Kue Tradisional dengan Bahan Dasar Tepung Ubi Jalar - Anita, Anita; Setyariningsih, Eny; Khanida, Marisha (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Sweet potato innovation increases public preference and can enter the modern market by being processed into modern cakes. Modern cake processing is made from local ingredients as a form of increasing the income of sweet potato farmers. Ummah Cookies is one of the pioneers of traditional sweet potato cake production. The purpose of this Community Service is to provide training in processing sweet potatoes into flour and direct application of sweet potato flour in making traditional cakes. Program evaluation includes assessment indicators regarding the understanding of the process of making sweet potato flour into flour, packaging and its application in making traditional cakes. Socialization activities, Training and Practice of making traditional cakes made from sweet potato flour went smoothly. The UNIM Community Service Team provided a live demonstration so that Ummah Cookies understood and were able to practice it independently. From the results of the Effect Evaluation (Pre-test and post-test) showed that the increase in partner capabilities was 4.21-89.2%. Making sweet potato flour at Itra Ummah Cookies showed a significant increase in partner knowledge and skills.